Emphasizing the role of AI and telehealth in improving treatment outcomes among elderly patients - Maryam Mojisola, Lasisi; Emmanuel Temitope, Adaranijo (Magyar Gerontológia, 2023)
To establish the right diagnosis and treatment plan for a patient is at the core of any medical procedure but this is not without the need for utmost compliance of the patient. This is the case with the elderly when they do not understand their diagnosis, nor do they fully recognize the importance of adhering to the prescribed treatment plan. This study emphasizes the role of artificial intelligence and telehealth in achieving significant treatment compliance among elderly patients.